Spatial and temporal distribution of infiltration, curve number and runoff coefficients using TOPMODEL and SCS-CN models - Mohammad Hossein Pishvaei; Shabnam Noroozpour; Touraj Sabzevari; Mostafa Akbari Kheirabadi; Andrea Petroselli (Journal of Agriculture and Environment for International Development)
Infiltration, the process by which water enters the soil, is intricately intertwined with the attributes of the catchment, including soil composition and vegetation cover, both of which exhibit temporal and spatial variability. Accurate quantification of infiltration rates is imperative for enhancing the predictive capabilities of rainfall-runoff models, especially in regions with limited hydrological monitoring infrastructure, such as many developing countries where a significant portion of catchments remains ungauged. In this study, we integrate the Soil Conservation Service Curve Number (SCS-CN) model with the TOPography-based hydrological MODEL (TOPMODEL) to derive a comprehensive framework for estimating the spatial and temporal dynamics of infiltration and its associated parameters. By leveraging the complementary strengths of these two models, we aim to enhance our understanding of infiltration processes across diverse landscapes. The amalgamation of the SCS-CN model with TOPMODEL Dynamic, which incorporates topographic features, contributing areas, and soil moisture deficit (SMD) dynamics within the watershed, represents a novel approach for characterizing the spatiotemporal variability of infiltration, curve number (CN), and runoff coefficient (RC). This integrated model offers a refined mathematical representation, capable of capturing the intricate interactions between land surface characteristics and hydrological processes, thereby advancing our ability to simulate and predict runoff responses in complex environmental settings.